Social Work & Corrections in the Progressive Era: What We Remember, What We Obscure. Issue 1 (2nd January 2023) - Harrell, Sam
ABSTRACT: Summary: The social work profession in the US developed alongside and within the professionalization of policing and corrections. Social workers are credited as some of the earliest policewomen, probation officers, and juvenile correctional facility superintendents. Still, our professional relationship to corrections in Progressive Era US history is underexplored and uninterrogated. How does this entangled history escape most narratives of professionalized social work in the US? This integrative literature review explores the stories social work scholars tell about social work's relationship(s) to corrections in the Progressive Era (1890–1930). Findings: Surveying 17 peer-reviewed social work articles, I identify themes of how social work remembers and obscures our Progressive Era relationship with corrections. Articles tell a story of delinquency, social control, and progress while obscuring the history of prisonwork, wardenship, and correctional leadership. Applications: Social work's professional memory of corrections in the early twentieth century has significant consequences for policy, research, and education today. Macro-level practitioners can learn from progressive reforms, engineered and implemented by early "reformers, " that widened the net of carceral control. Further research is needed to explore social work's correctional history, prisonwork in particular. This may be taken up in the form of archival research and oral histories.